Contribution of Non-Timber Forest Products (NTFPS) to the Income of Forest Edge Farmers in Community Forests (HKM) Aik Berik Village, North Batukliang District, Central Lombok Regency - Hafiz, I Abdul; Ansyar, Muh.; Hermawan, Yudi (Implikasi: Jurnal Manajemen Sumber Daya Manusia, 2023)
The research was conducted in the Community Forest Area (HKm) of Aik Berik Village, North Batukliang Subdistrict, Central Lombok Regency, with the aim of determining the income of community forest farmers from non-timber forest products and paddy farming. Additionally, the study aimed to analyze the contribution of non-timber forest products to the income of paddy farming in the community. The objectives of this research were to identify the types of Non-Timber Forest Products (NTFPs) most utilized by Community Forest Farmers in Aik Berik Village, analyze the contribution of NTFPs to farmer income, and evaluate the constraints affecting the utilization of NTFPs in the HKm of Aik Berik Village. The research method used was descriptive with purposive sampling. The results showed that durian, banana, avocado, and taro were the most used NTFPs by farmers. The average income of farmers reached IDR 35,857,179 per year, with NTFPs contributing 70.04% to the total income. This contribution reflects the significant role of NTFPs in improving the welfare of farmers and the economic sustainability on the outskirts of forest areas. Constraints such as weather, market fluctuations, and price instability influence farmers' income in using NTFPs. This study provides important insights for the management of NTFP resources in HKm and promotes economic sustainability for communities on the forest edge.